1998
DOI: 10.1103/physrevlett.80.4064
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Single Molecule Spectroscopy

Abstract: A new method based on the calculation of autocorrelation functions for spectra measured at a high acquisition rate is developed to study spectral dynamics of single molecules. The technique allows for spectroscopy with time resolutions down to the luminescence lifetime. The method is used to study spectral diffusion in two-photon excitation spectra of diphenyloctatetraene molecules doped in an n-tetradecane crystal matrix. The diffusion is light induced, and is absent in one-photon excitation spectra. It has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…For ZPLs which jump on a small energy scale of a few wavenumbers, it has been demonstrated that even fast jumps can be resolved with high temporal resolution using intensity-time-frequency correlations. [4] To date, it was however not possible to use excitation spectroscopy for the investigation of systems in which frequent and far-spectral ZPL jumps occur. Unfortunately, many interesting systems such as dye-doped polymers or chromophore containing proteins fall into this category.…”
Section: Introductionmentioning
confidence: 99%
“…For ZPLs which jump on a small energy scale of a few wavenumbers, it has been demonstrated that even fast jumps can be resolved with high temporal resolution using intensity-time-frequency correlations. [4] To date, it was however not possible to use excitation spectroscopy for the investigation of systems in which frequent and far-spectral ZPL jumps occur. Unfortunately, many interesting systems such as dye-doped polymers or chromophore containing proteins fall into this category.…”
Section: Introductionmentioning
confidence: 99%
“…[64] More recently, it was applied to model SMS in low temperature glass systems in order to describe the static properties of line shapes [14,15,16,65] and also to model the time dependent fluctuations of SMS. [66,67,68] Mandel's Q parameter quantitatively describes the deviation of the photon statistics from the Poissonian case [69,70],…”
Section: Introductionmentioning
confidence: 99%
“…SD can be studied using either conventional spectroscopic technique, which is based on the acquisition of consecutive photoluminescence (PL) spectra [13], or by more advanced methods. Due to practical limitations linked to the collection efficiency of the experimental setup, high resolution spectroscopic techniques have to be used on faster time scales than few ms. Plakhotnik et al were the pioneers of fast spectroscopic techniques [15]. From 1998, other experimental techniques were developed.…”
Section: Introductionmentioning
confidence: 99%